2011
DOI: 10.1016/j.visres.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of retinal adaptive circuitry in the myopic eye

Abstract: Previous studies have proposed that the inner retina is affected in myopes. This study aimed to investigate the changes in adaptive circuitry of the inner retina in myopia, using the global flash multifocal electroretinogram (global flash mfERG) with different levels of contrast (luminance modulation). Fifty-four myopes had global flash mfERG recorded with different contrasts. The direct component (DC) and the induced component (IC) of the mfERG response were pooled into six regions for analysis. The response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 80 publications
(124 reference statements)
4
20
0
Order By: Relevance
“…This finding is consistent with the finding of Chen et al 22 that refractive error accounted for a greater proportion of the variability than axial length in mfERG responses in myopic adults. The studies of Ho et al 5,6 used a hierarchical regression model that evaluates the individual effect of both variables and these researchers also showed that refractive error contributed most of the reduction in ERG response in adults. In our study, we calculated the 1-year changes in refractive error (À0.55 6 0.53 D) and axial length (0.37 6 0.22 mm) of young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the finding of Chen et al 22 that refractive error accounted for a greater proportion of the variability than axial length in mfERG responses in myopic adults. The studies of Ho et al 5,6 used a hierarchical regression model that evaluates the individual effect of both variables and these researchers also showed that refractive error contributed most of the reduction in ERG response in adults. In our study, we calculated the 1-year changes in refractive error (À0.55 6 0.53 D) and axial length (0.37 6 0.22 mm) of young children.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that myopia in adults was associated with decreased nonlinear components of ERG responses, 1 multifocal ERG (mfERG) responses, 2,3 retinal adaptation response, 4 and inner retinal function. [5][6][7] Axial length was shown to be linearly related to ERG amplitudes, 8 first-order kernel, and the first slice of second-order kernel of mfERG responses. 9 The reduction in mfERG responses in myopic adults is believed to be due to the deterioration in retinal function associated with long-standing myopia.…”
mentioning
confidence: 96%
“…The multifocal electroretinogram (mfERG) measures retinal function of multiple loci simultaneously and can detect localized defects within the central retinal field. 6 Many authors [7][8][9][10] have also reported reduced and delayed mfERG responses in myopic adults, especially in the paracentral region. Interestingly, Luu and coworkers 11 have found that the mfERG response is affected by the magnitudes of myopia in adults but not in children, which implies that the effect of myopia on the retinal function is not the same between children and adults.…”
Section: Resultsmentioning
confidence: 99%
“…The paracentral retina has been shown to be affected in adult myopes. 9 The present study aimed to investigate the regional changes of retinal function in children during myopia progression. The global flash mfERG with different contrast stimulation was used to separate the inner and outer retinal activities to the mfERG response.…”
Section: Resultsmentioning
confidence: 99%
“…Does the human eye have a particular zone of the retina which guides refractive development? Avery recent study from Ho and co-workers may provide some hints [4]. They applied the electroretinogram to study retinal function in myopic human eyes.…”
mentioning
confidence: 99%